THE BENEFITS OF EDUCATION IN MOTHER TONGUE - Akhmadova Maftuna Ibodullo qizi Saydulloyeva Tamanno Xayriddinovna (Research Focus International Scientific Journal, 2025)
Education in the mother tongue plays a crucial role in cognitive development, academic achievement, and cultural preservation. This article explores the advantages of learning in one’s native language, including improved comprehension, better problem-solving skills, and enhanced emotional connection to learning. It also examines the impact of mother tongue education on literacy, creativity, and social integration. By comparing mother tongue-based instruction with foreign language-based education, the paper highlights the importance of linguistic identity and offers recommendations for policymakers and educators to promote effective language policies.